Municipal level water security indices in Mexico - Arreguin-Cortes, Felipe I.; Saavedra-Horita, J. Raul; Rodriguez-Varela, J. Manuel; Tzatchkov, Velitchko G.; Cortez-Mejia, Petronilo E.; Llaguno-Guilberto, Oscar J.; Sainos-Candelario, Arizabeth; Sandoval-Yoval, Luciano; Ortega-Gaucin, David; Mendoza-Cazares, E. Yuri; Navarro-Barraza, Salvador (SN applied sciences, 2019)
As tends to be the case in other large, developing countries, Mexico is a nation of strong meteorological, hydrographic and social contrasts throughout its territory, which impact the various strata of the population in different ways. The current paper seeks to show how these contrasts create different water-security scenarios using pertinent indices. While some of the impact factors, such as precipitation, drought and floods, are of intrinsically probabilistic nature, others are related to population vulnerability. There have been a small number of studies on water security at global or regional scale that include Mexico, or at local level in Mexico, but none of them consider probabilistic aspects and population vulnerability, neither extend to municipal level. A probabilistic methodology was defined in this paper, and applied at municipal scale in Mexico, to obtain a water security index, which considers the concepts of risk, hazard and social vulnerability. Hazard comes in the form of water supply and drainage shortage, flooding, pollution, water quality, groundwater depletion and drought indicators. Vulnerability considers factors such as the educational level of the population, access to health services, illiteracy, housing conditions, unemployment and the proportion of indigenous language population. All these indicators are very heterogeneous throughout the Mexican territory. The proposed probabilistic methodology was applied in a geographic information system environment, and it was used to obtain water security indices for all municipalities in Mexico (2456 municipalities).